On Fuzzy Positive Implicative Filters in BE-Algebras - Sun Shin Ahn; Jeong Soon Han (The Scientific World Journal)
We study several degrees in defining a fuzzy positive implicative filter, which is a generalization of a fuzzy filter in BE-algebras.